Manajemen Pelayanan Jamaah Haji Dan Umrah Dalam Menyesuaikan Kenaikan Biaya Haji Dan Umrah PT. Bumi Nata Wisata Palembang - Dita Indriani; candra Darmawan (ScidacPlus, 2023)
ABSTRACT: This research discusses “Service Management for Hajj and Umrah Pilgrims in Adjusting to the Increase in Hajj and Umrah Costs PT. Bumi Nata Wisata Palembang” This research aims to determine the service management that will be provided to determine the supporting and inhibiting factors in carrying out Hajj and Umrah services. This type of research is qualitative research, with secondary and primary data sources. Data collection techniques use observation, interviews and documentation. The data analysis technique in this research is descriptive qualitative by means of data reduction, data presentation, and drawing conclusions. The results obtained from the research are that there are six stages of the theory put forward by Dr. H. Tata Sukayat, M.Ag: The management that has been planned: recruiting good, friendly and responsive human resources who have skills, providing training to employees, providing guidance and training to the congregation, as well as providing information services and ease of payment . The supporting and inhibiting factors in carrying out Hajj and Umrah services are the location of the office which is strategic and easy to reach for pilgrims. Meanwhile, the obstacle in the service process is the lack of human resources or employees at PT. Bumi Nata Wisata, lacks indoor facilities and the office is very cramped, and there are many personal documents out of sync with prospective Hajj and Umrah pilgrims, making the administration process difficult. Service management carried out by PT. Bumi Nata Wisata. Keywords: Service management, Increase in Hajj and Umrah costs